2010
DOI: 10.2147/ijn.s15033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver/montmorillonite nanocomposites using γ-irradiation

Abstract: Silver nanoparticles (Ag-NPs) were synthesized into the interlamellar space of montmorillonite (MMT) by using the γ-irradiation technique in the absence of any reducing agent or heat treatment. Silver nitrate and γ-irradiation were used as the silver precursor and physical reducing agent in MMT as a solid support. The MMT was suspended in the aqueous AgNO 3 solution, and after the absorption of silver ions, Ag + was reduced using the γ-irradiation technique. The properties of Ag/MMT nanocomposites and the diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 64 publications
1
58
0
Order By: Relevance
“…Incorporation of silver nanoparticles into biopolymer chitosan resulting in silver-chitosan nanocomposites is interesting to study due to their high antibacterial activity [2][3]. They can be synthesized using various methods, such as chemical reduction [3][4], electrochemical [5], γ-radiation, [6] photochemical [7] and laser ablation [8]. However, the most popular preparation of silver colloids is chemical reduction or "wet" chemical reduction of silver ions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of silver nanoparticles into biopolymer chitosan resulting in silver-chitosan nanocomposites is interesting to study due to their high antibacterial activity [2][3]. They can be synthesized using various methods, such as chemical reduction [3][4], electrochemical [5], γ-radiation, [6] photochemical [7] and laser ablation [8]. However, the most popular preparation of silver colloids is chemical reduction or "wet" chemical reduction of silver ions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on talc/Fe 3 O 4 -NCs (Kalantari et al 2013a,b), rice straw/Fe 3 O 4 -NCs , zeolite/Fe 3 O 4 -NCs (Jahangirian et al 2013), and other nanoparticles such as silver in talc (Shameli et al 2010a), montmorillonite (Shameli et al 2010b, Ahmad et al 2009a, Ahmad et al 2009b, zeolite , montmorillonite/starch (Ahmad et al 2010), chitosan (Ahmad et al 2009cShameli et al 2011b), polyethylene glycol (Shameli et al 2012a,b), plant extract (Shameli et al 2012c,d), and polymeric substrate (Shameli et al 2011c), have been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…These classifications are described as nanocomposites (NCs). 3 There are different types of NCs depending on the phases of constituents, eg, metal/polymer, 4 metal/metal, 5 metal/metal oxides, 6 metal/clay, 7,8 and metal/zeolite.…”
Section: Introductionmentioning
confidence: 99%